2022
DOI: 10.1111/bjh.18531
|View full text |Cite
|
Sign up to set email alerts
|

Thymic stromal lymphopoietin induces platelet mitophagy and promotes thrombosis in Kawasaki disease

Abstract: Kawasaki disease (KD) is an acute systemic vasculitis primarily affecting infants and children. Activated platelets predispose patients to coronary artery structural lesions that may lead to thrombotic cardiovascular events. To discover potential proteins underlying platelet activation in KD, we conducted a protein chip assay of 34 cytokines and discovered thymic stromal lymphopoietin (TSLP) was aberrantly expressed, which remained elevated after intravenous immunoglobulin G (IVIG) treatment and during convale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Rick Kapur may result in thrombotic cardiovascular events. 8 The authors previously reported elevated levels of soluble CD40L and soluble P-selectin in plasma of KD patients, positively correlated with the degree of coronary artery damage. 9 In the current study they confirmed these findings, and additionally found an elevation for the platelet activation marker P-selectin, in acute KD (before and after IVIg) and convalescent patients compared to healthy controls.…”
Section: Platelet Activation and Mitophagy Induction By Thymic Stroma...mentioning
confidence: 95%
See 1 more Smart Citation
“…Rick Kapur may result in thrombotic cardiovascular events. 8 The authors previously reported elevated levels of soluble CD40L and soluble P-selectin in plasma of KD patients, positively correlated with the degree of coronary artery damage. 9 In the current study they confirmed these findings, and additionally found an elevation for the platelet activation marker P-selectin, in acute KD (before and after IVIg) and convalescent patients compared to healthy controls.…”
Section: Platelet Activation and Mitophagy Induction By Thymic Stroma...mentioning
confidence: 95%
“…In their paper, Fu and colleagues postulate that activated platelets may predispose to coronary artery lesions that may result in thrombotic cardiovascular events 8 . The authors previously reported elevated levels of soluble CD40L and soluble P‐selectin in plasma of KD patients, positively correlated with the degree of coronary artery damage 9 .…”
mentioning
confidence: 99%
“…Platelet activation and abnormal iron metabolism accelerated thrombosis and induced oxidative stress as well as death in the vascular wall. [ 220 , 309 , 310 ] Atherosclerosis Apoptosis, ferroptosis, pyroptosis Foam cells had abnormal lipid metabolism, and inhibition of autophagy aggravated atherosclerosis. Altering mitochondrial dynamics stimulated mitochondrial autophagy and abnormal cell proliferation of VSMCs, thereby aggravating atherosclerosis.…”
Section: Relevant Clinical Diseasesmentioning
confidence: 99%
“…Through the combined action of various factors, VSMCs undergo iron overload and death, affecting vascular endothelial integrity. In addition, thymic stromal lymphopoietin is significantly elevated in patients, and it induces platelet activation via mitophagy agonists, contributing to thrombosis [ 220 ].…”
Section: Relevant Clinical Diseasesmentioning
confidence: 99%